1990
DOI: 10.1136/jech.44.4.286
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cancer of the buccal and labial mucosa in Kerala, southern India.

Abstract: Study objective-The aim was to investigate risk factors for cancer of the buccal and labial mucosa in Kerala, southern India.Design-The investigation was a casecontrol study.Setting-Regional Cancer Centre, Trivandrum, Kerala, and local teaching hospitals.Participants-Cases were all those registered with oral cancers at the Regional Cancer Centre during 1983 and 1984 (n = 414). Controls (n = 895) were selected from admissions to the cancer centre who were found to have non-malignant conditions, or from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
97
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 13 publications
11
97
1
Order By: Relevance
“…Beedi smokers were at a greater risk than cigarette smokers in this study. This is similar to the findings of Sankarnarayan et a1 who have reported greater risk for bidi smokers than cigarette smokers for cancer of the buccal and labial mucosa [14], esophagus [15], and lar› ynx [16]. Quid chewers were found to be at greater risk of upper aero digestive cancers than non chewers in this study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Beedi smokers were at a greater risk than cigarette smokers in this study. This is similar to the findings of Sankarnarayan et a1 who have reported greater risk for bidi smokers than cigarette smokers for cancer of the buccal and labial mucosa [14], esophagus [15], and lar› ynx [16]. Quid chewers were found to be at greater risk of upper aero digestive cancers than non chewers in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Quid chewing has long been held responsible for the high incidence of upper aero digestive cancer in India. Simi› lar findings have been reported by Sankar› narayan et al [14] and Iayant et al [17]. Signifi› cant association between quid chewing and oral and pharyngeal cancer has also been reported by Shanta [10], and Jussawalla [18].…”
Section: Discussionsupporting
confidence: 64%
“…Tobacco chewing and smoking have been identified as the major risk factors for these cancers in India. 15,[17][18][19] Cancers of the oral cavity occupy the second-highest position among males in Kolkata. The prevalent chewing habits involve use of betel quid (betel leaf with tobacco, areca nut, lime), gutkha (dried mixture of betel quid and tobacco sold in attractive pouches), mawa and zarda (flavoured tobacco) or khaini (crude form of dried ground tobacco with lime).…”
Section: Discussionmentioning
confidence: 99%
“…This ratio seems to be vary from one study to the other in India for example, Sankaranarayanan et al (1990) has reported almost the same ratio (2:1) and Mehrotra et al (2003) has shown higher ratio (3.27); while lower ratios have been reported by Chattopadhyay (1989) (1.76:1). It may be due to the more exposure to risk factors such as tobacco and alcohol by men compare to women.…”
Section: Discussionmentioning
confidence: 64%